IMPLEMENTASI PROGRAM PLAY THERAPY UNTUK MENGURANGI TINDAKAN KEKERASAN PADA ANAK INDONESIA - Darmin Tuwu (Journal Publicuho, 2025)
Violence against children remains a serious problem in Indonesia's social welfare system. This study aims to analyse the implementation of play therapy programs as a psychosocial intervention strategy to reduce the impact of violence against children. Using a qualitative approach with a case study design, the research was conducted at a Child Social Welfare Institution in Yogyakarta through in-depth interviews, participatory observation, and document analysis. The results showed that play therapy was effective in reducing aggressive behaviour, improving emotional expression, and strengthening children's sense of security after trauma. Social workers act as therapeutic mediators who bridge children's emotional recovery with the support of family and social environment. Local cultural adaptation through traditional games increases the acceptance and effectiveness of therapy. However, limited human resources and national guidelines are major obstacles to implementation. This study emphasises the importance of developing a play-based and locally cultural intervention model as part of child social rehabilitation services in Indonesia.